Improving Characteristics of FSMs With Mixed Codes of Outputs - Alexander Barkalov; Larysa Titarenko; Slawomir Chmielewski; Kamil Mielcarek (IEEE Access, 2022)
Practically, any digital system includes sequential blocks. This paper considers a case when LUT-based sequential blocks are represented by Mealy finite state machines (FSMs). The LUT count is one of the most important characteristics of an FSM circuit. In this paper, a method is proposed which aims at decreasing the LUT counts of FPGA-based Mealy FSMs with mixed encoding of the collections of outputs. To do it, a method of encoding of the fields of compatible states is proposed. The proposed approach leads to LUT-based Mealy FSM circuits having three levels of logic blocks. Each function for any logic level is represented by a circuit including a single LUT. There is given an example of FSM synthesis with the proposed method. The experiments are conducted using standard benchmark FSMs. The results of experiments show that the proposed approach produces LUT-based circuits with fewer LUTs than it is for circuits produced by other investigated methods (Auto and One-hot of Vivado, JEDI, the mixed encoding the collections of outputs). The LUT count is decreased by an average of 6.97 to 62.85 percent. These improvements are accompanied by a slight decrease in the maximum operating frequency. The frequency is decreased by up to 8.09%. The advantages of the proposed method increase as the number of FSM inputs and states increases.